(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2023)
Functional analytic psychotherapy (FAP) provides a behavioral analysis of the psychotherapy relationship that directly applies basic research findings to outpatient psychotherapy settings. Specifically, FAP suggests that a therapist’s in vivo (i.e., in-session) contingent responding to targeted client behaviors, particularly positive reinforcement of a client’s effective behavior, should be a powerful mechanism of change. However, much of the previous literature on FAP has been theoretical, broadly defining FAP techniques rather than explicating them with the precision necessary for replication and training. In this article, the authors explicate a logical framework for turn-by-turn interactions between the client and therapist that may guide research, training, and dissemination of FAP. This molecular behavioral description of the events of the proposed logical interaction lends itself to microprocess research methodology, and a discussion of potential hypotheses to explore follows. Prescriptive, direct guidance for the application of FAP for training and dissemination purposes is given.